2001
DOI: 10.1002/jemt.1130
|View full text |Cite
|
Sign up to set email alerts
|

FMRFamide in the amphibian brain: A comprehensive survey

Abstract: Mapping of FMRFamidergic neural circuitry in the amphibian brain has been done by immunohistochemical methods. Comparative evidence suggests that there are similarities and differences in the overall pattern of distribution of FMRFamide-ir elements in the brain among the three amphibian orders and within each order. FMRFamide is expressed in neurons in some circumscribed areas of the brain. A part of these neurons is concentrated in classical neurosecretory areas of the hypothalamus in a bilaterally symmetrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 72 publications
3
42
0
Order By: Relevance
“…The relationship between Drosophila insulin-like peptides and AKH (Kim & Rulifson 2004) is most likely homologous to the antagonism between glucagon and insulin in vertebrates. There exist a number of other neuropeptides, among them FMRFamides (Rastogi et al 2001, Nassel 2002, tachykinins (Nussdorfer & Malendowicz 1998) and CRF/CRF-like diuretic hormone (Schoofs et al 1997, Nassel 2002 found in vertebrate hypothalamus and insect PI.…”
Section: Similarities In Structure and Functionmentioning
confidence: 99%
“…The relationship between Drosophila insulin-like peptides and AKH (Kim & Rulifson 2004) is most likely homologous to the antagonism between glucagon and insulin in vertebrates. There exist a number of other neuropeptides, among them FMRFamides (Rastogi et al 2001, Nassel 2002, tachykinins (Nussdorfer & Malendowicz 1998) and CRF/CRF-like diuretic hormone (Schoofs et al 1997, Nassel 2002 found in vertebrate hypothalamus and insect PI.…”
Section: Similarities In Structure and Functionmentioning
confidence: 99%
“…The molluscan neuropeptide Phe-Met-Arg-Phe-NH 2 (FMRFa) was discovered in the ganglia of the venus clam (Price & Greenberg 1977), and it was suggested that the vertebrate hypothalamus possesses some unknown neuropeptides similar to FMRFa (Raffa 1988, Rastogi et al 2001). In fact, over the past decade, neuropeptides that have the ArgPhe-NH 2 (RFa) motif at their C-termini have been identified in the brains of several vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…The molluscan cardioexcitatory neuropeptide Phe-Met-Arg-Phe-NH2 (FMRFamide) was first found in the ganglia of the venus clam Macrocallista nimbosa [47], and RFamide peptides were subsequently characterized in various other invertebrates. Immunohistochemical studies using an antiserum against FMRFamide suggested the presence of uncharacterized RFamide peptides in vertebrate nervous systems [49,50]. Some of the FMRFamide-like immunoreactive neurons were seen to project to the hypothalamic region close to the pituitary gland, and were thus predicted to play a role in the regulation of pituitary function.…”
Section: Brief History and Identification Ofmentioning
confidence: 99%